One last secret eaudiobook - Parks, Adele (Harlequin Audio, 2022)
"I'll drop anything for a new Adele Parks: she nails it every time"—Lucy Foley, #1 New York Times bestselling author of The Paris Apartment "Absolutely gripping"—Lisa Jewell, New York Times bestselling author of The Family Remains "Whip-smart protagonist, immensely satisfying"—Karin Slaughter, New York Times bestselling author of Girl, Forgotten "Parks gets better and better"—Gillian McAllister, New York Times bestselling author of Wrong Place Wrong Time Everyone has secrets, don't they? One last client A week at a beautiful chateau in the south of France—it should be a straightforward final job for Dora. She's a smart, stunning and discreet escort, and Daniel has paid for her services before. This time, all she has to do is to convince the assembled guests that she is his girlfriend. Dora is used to playing roles and being whatever men want her to be. It's all about putting on a front. One last chance It will be a last, luxurious look at how the other half lives before Dora turns her back on the escort world and all its dangers. She has found someone she loves and trusts. With him, she can escape the life she's trapped in. But when Dora arrives at the chateau, it quickly becomes obvious that nothing is what it seems... One last secret Dora finds herself face-to-face with a man she has never forgotten, the one man who really knows her. And as old secrets surface, it becomes terrifyingly apparent that one last secret could cost Dora her life... From the Sunday Times number one bestseller Adele Parks comes a blisteringly provocative novel about power, sex, money and revenge. In bestselling author Adele Park's new thriller, FIRST WIFE'S SHADOW, a woman meets and marries a handsome widower...but things begin to take dark, dangerous turns and she's left wondering who she can trust: her friends, her husband, or even herself...? Don't miss these other pulse-pounding thrillers from Adele Parks: Two Dead Wives Woman Last Seen The Image of You Lies Lies Lies I Invited Her In Just My Luck